(untitled) (Clinics, 2013)
OBJECTIVE: To assess the effectiveness of healthcare team guidance in the implementation of a glycemic control protocol in the non-intensive care unit of a cardiology hospital. METHODS: This was a randomized clinical trial comparing 9 months of intensive guidance by a healthcare team on a protocol for diabetes care (Intervention Group, n = 95) with 9 months of standard care (Control Group, n = 87). Clinicaltrials.gov: NCT01154413. RESULTS: The mean age of the patients was 61.7±10 years, and the mean glycated hemoglobin level was 71±23 mmol/mol (8.7±2.1%). The mean capillary glycemia during hospitalization was similar between the groups (9.8±2.9 and 9.1±2.4 mmol/l for the Intervention Group and Control Group, respectively, p = 0.078). The number of hypoglycemic episodes (p = 0.77), hyperglycemic episodes (47 vs. 50 in the Intervention Group and Control Group, p = 0.35, respectively), and the length of stay in the hospital were similar between the groups (p = 0.64). The amount of regular insulin administered was 0 (0-10) IU in the Intervention Group and 28 (7-56) IU in the Control Group (p